E-SUPERVISION OF STUDENTS’ RESEARCH WRITING IN NIGERIAN OPEN AND DISTANCE EDUCATIONAL INSTITUTIONS: CHALLENGES AND PROSPECTS - FASASI Yunus Adebunmi; Sulaimon Yunus Adebunmi (International Journal of Distance Education and E-Learning, 2018)
Research is an aspect of the academic programme which students in tertiary educational institutions are expected to undergo. It involves identification, investigation and suggestion of solutions to societal developmental problems. Higher education students in open and distance learning institutions and centers make use of print and electronic media in knowledge and skill acquisition with minimal physical contact. Their research activities are also electronically supervised. This paper examines prospects and challenges of using electronic method of research project supervision in Nigeria. It also discusses the roles of a supervisor in assisting distance learners to achieve the objectives of conducting an academic research. More funding of ICT education for lecturers and students, Public and Private Partnership (PPP) for the provision of facilities among others were recommended by this study to ameliorate the challenges of E-supervision in Nigerian higher institutions.